The potential of hydrellia egeriae rodrigues (diptera: ephydridae) as a biocontrol agent for egeria densa planch. (hydrocharitaceae) in South Africa - Smith, Rosali (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2017)
The integrity of South Africa's valuable freshwater ecosystems has been threatened by aquatic invasive plants since the 1900s. Floating aquatic weeds, such as Eichhornia crassipes (C. Mart) Solms (Pondederiaceae), Pistia stratiotes L. (Araceae), Salvinia molesta D.S. Mitchell (Salviniaceae), Azolla filiculoides Lam. (Azollaceae), and the emergent weed, Myriophyllum aquaticum Verdc. (Haloragaceae) benefited from open, nutrient-rich water bodies. Due to the limitations of mechanical and chemical control in aquatic environments, classical biological control has been a huge asset in managing these weeds; consequently bringing them under complete or substantial control. However, submerged aquatic weeds are widely distributed through the aquarium trade in South Africa; facilitating their invasion into new habitats. The removal of surface mats following the successful management of floating weeds has enhanced the growth and competitive ability of submerged aquatic weeds, such as Hydrilla verticillata (L.f.) Royle (Hydrocharitaceae), Myriophyllum spicatum L. (Haloragaceae) and Egeria densa Planch. (Hydrocharitaceae) in South Africa. Of these species, E. densa has become the most widely distributed, invading numerous systems across South Africa. Compared to other exotic submerged aquatic plants, E. densa is the only species capable of inhabiting freshwater systems in every province and therefore, it is vital to manage existing populations and prevent its further distribution and invasion. Hydrellia spp. (Diptera: Ephydridae) biological control agents have been used extensively in the management of submerged aquatic weeds elsewhere, particularly those in the Hydrocharitaceae (Balciunas and Burrows 1996; Wheeler and Center 2001. Hydrellia egeriae Rodrigues (Diptera: Ephydridae) has been identified as a promising candidate for E. densa and was imported into quarantine at Rhodes University, Grahamstown in 2014. The aims of this study were to conduct a pre-release assessment of the potential of H. egeriae as a biological control agent for E. densa in South Africa. The first objective of this study was to establish the life history of the agent under controlled conditions on E. densa found in South Africa, as well as its population growth parameters to predict its invasion success in the field. Secondly, laboratory host-specificity testing was conducted to validate the host range of the agent, in view of published native range host-specificity testing, and to establish potential risks to non-target species, should it be released. Finally, a biological control agent should also effectively reduce the fitness of its host plant, and therefore, impact studies were conducted. Laboratory impact studies have been limited in the past, in that they only investigate agent damage for short ecological periods, thus underestimating the damage capacity of the agent under investigation. Therefore, the damage capacity of H. egeriae was investigated over three consecutive generations in multi-generational impact trials. In a controlled environment of 22 Â± 2Â°C, H. egeriae exhibited the ability to rapidly increase in population size within a short period of time, which will enhance agent establishment and build-up in the field. Host-specificity trials indicated that H. egeriae has a host range restricted to the Hydrocharitaceae, with exploratory feeding and development on Lagarosiphon major Ridley, L. muscoides Harvey and Vallisneria spiralis L. However, only L. major supported agent development during paired larval choice tests, and continuation trials showed that the test species was not physiologically capable of supporting viable agent populations. Risk analysis illustrated that the feeding and reproductive risks that H. egeriae pose to non-target species are very low and therefore, H. egeriae should be safe for release in South Africa. Additionally, significant damage to vital plant structures (shoot growth and side shoot length) was only recorded under high (five larvae) agent abundances. Encouragingly, the number of leaves mined at the end of the experiment was similar for both intermediate (three) and high (five) larval abundances, suggesting that cumulative leaf-mining under intermediate larval abundances has the potential to reduce the fitness of E. densa, given sufficient time. Results from pre-release assessments provide a robust understanding of the specialization of the potential biological control agent to its host plant. Nevertheless, the absolute success of a biological control programme depends on the many factors after prerelease assessments that determine agent establishment, persistence and target weed suppression, e.g. mass-rearing, release protocols and a/biotic factors within the recipient community. Considering these factors, the best mass-rearing and release protocols are proposed here and future research priorities are identified. Finally, the long term success for managing E. densa in South Africa will require a holistic approach to address the underlying factors, such as eutrophication and human-mediated distribution that drive submerged aquatic plant invasions.
Keywords: Uncatalogued